Demand for off-grid solar electricity: Experimental evidence from Rwanda - Michael Grimm; Luciane Lenz; Jörg Peters; Maximiliane Sievert (RWI - Leibniz-Institut für Wirtschaftsforschung, 2018)
The cost of providing electricity to the unconnected 1.1 billion people in developing countries is significant. High hopes are pinned on market-based dissemination of offgrid technologies to complement the expensive extension of public grid infrastructure. In this paper, we elicit the revealed willingness-to-pay for different off-grid solar technologies in a field experiment in rural Rwanda. Our findings show that households are willing to dedicate substantial parts of their budget to electricity, but not enough to reach cost-covering prices. Randomly assigned payment periods do not alter this finding. We interpret the results from two perspectives. First, we examine whether the United Nations' universal energy access goal can be reached via unsubsidized markets. Second, in a stylized welfare cost-benefit analysis, we compare a subsidization policy for off-grid solar electrification to a grid extension policy. Our findings suggest that, for most of rural Africa, off-grid solar is the preferable technology to reach mass electrification, and that grid infrastructure should concentrate on selected prosperous regions.
Keywords: D12; H54; O13; Q28; Q41; 330; public infrastructure; technology adoption; electrification; willingness-to-pay; energy access